L'affidamento familiare: le strategie educative elaborate dagli affidatari - Paola Ricchiardi; Cristina Coggi (LED Edizioni Universitarie, 2021)
Foster care is a condition of welcoming children with families in serious difficulty, legally regulated, aimed at guaranteeing to minors a suitable space for growth, and to families of origin the possibility of overcoming the problems so as to consent the return of the children. It is a challenging educational condition, to be deepened with research. The complexity of the backgrounds of origin and the co-presence of multiple risk factors in fact generate in children and young people in foster care, important difficulties in development, which foster families have to cope with, also with the support of specialists, services and associations. However, the skills that caregivers come to build over the years are valuable, deserving of pedagogical insights, so that good practices of positive parenting can be valued and shared. In this paper we will report the results of a survey, carried out with a national sample of 323 foster families. The study makes it possible to investigate the reasons for the custody prevision, the relationships with families of origin, the difficult life trajectories of the children in foster care (transitions, placements, discontinuities, years of foster care, continuation of relationships after foster care). In this way it is possible to identify the needs highlighted by the minors, the relevant problems that emerge and the promising strategies adopted by the foster families.